Peripheral Cluster versus New Town: A Comparative Study on Two Types of Peripheral Developments in the Beijing Metropolitan Region - Jing Zhou; Lei Qu (Footprint)
Spatial decentralisation has been a planning goal for Beijing city since 1950s. It had not been fully activated until the mid-1990s, when the suburbanisation process started to accelerate rapidly. Under the influence of joint forces of top-down intervention and market-driven development, several large-scale peripheral clusters and new towns have been built in both near and far suburbs. However, the spatial structure of the city remains to be rather mono-centric, which causes severe urban and environmental problems. In the latest Beijing Master Plan, the metropolitan region is considered as a whole. A polycentric spatial structure is proposed with the aim to consolidate the existing regional centralities as stronger counter-weights to central city.